Analysis of the miRNA expression from the adipose tissue surrounding the adrenal neoplasia - Antonio Concistrè; Luigi Petramala; Francesco Circosta; Priscilla Romagnoli; Maurizio Soldini; Marco Bucci; Domenico De Cesare; Giuseppe Cavallaro; Giorgio De Toma; Francesco Cipollone; Claudio Letizia (Frontiers in Cardiovascular Medicine, 2022)
BackgroundPrimary aldosteronism (PA) is characterized by several metabolic changes such as insulin resistance, metabolic syndrome, and adipose tissue (AT) inflammation. Mi(cro)RNAs (miRNAs) are a class of non-coding small RNA molecules known to be critical regulators in several cellular processes associated with AT dysfunction. The aim of this study was to evaluate the expression of some miRNAs in visceral and subcutaneous AT in patients undergoing adrenalectomy for aldosterone-secreting adrenal adenoma (APA) compared to the samples of AT obtained in patients undergoing adrenalectomy for non-functioning adrenal mass (NFA).MethodsThe quantitative expression of selected miRNA using real-time PCR was analyzed in surrounding adrenal neoplasia, peri-renal, and subcutaneous AT samples of 16 patients with adrenalectomy (11 patients with APA and 5 patients with NFA).ResultsReal-time PCR cycles for miRNA-132, miRNA-143, and miRNA-221 in fat surrounding adrenal neoplasia and in peri-adrenal AT were significantly higher in APA than in patients with NFA. Unlike patients with NFA, miRNA-132, miRNA-143, miRNA-221, and miRNA-26b were less expressed in surrounding adrenal neoplasia AT compared to subcutaneous AT in patients with APA.ConclusionThis study, conducted on tissue expression of miRNAs, highlights the possible pathophysiological role of some miRNAs in determining the metabolic alterations in patients with PA.